The association of depression and anxiety with pain: a study from NESDA. - Eric W de Heer (Public Library of Science (PLoS), 2014)
Chronic pain is commonly co-morbid with a depressive or anxiety disorder. Objective of this study is to examine the influence of depression, along with anxiety, on pain-related disability, pain intensity, and pain location in a large sample of adults with and without a depressive and/or anxiety disorder. The study population consisted of 2981 participants with a depressive, anxiety, co-morbid depressive and anxiety disorder, remitted disorder or no current disorder (controls). Severity of depressive and anxiety symptoms was also assessed. In separate multinomial regression analyses, the association of presence of depressive or anxiety disorders and symptom severity with the Chronic Pain Grade and location of pain was explored. Presence of a depressive (OR = 6.67; P<.001), anxiety (OR = 4.84; P<.001), or co-morbid depressive and anxiety disorder (OR = 30.26; P<.001) was associated with the Chronic Pain Grade. Moreover, symptom severity was associated with more disabling and severely limiting pain. Also, a remitted depressive or anxiety disorder showed more disabling and severely limiting pain (OR = 3.53; P<.001) as compared to controls. A current anxiety disorder (OR = 2.96; p<.001) and a co-morbid depressive and anxiety disorder (OR = 5.15; P<.001) were more strongly associated with cardio-respiratory pain, than gastro-intestinal or musculoskeletal pain. These findings remain after adjustment for chronic cardio respiratory illness. Patients with a current and remitted depressive and/or anxiety disorder and those with more severe symptoms have more disabling pain and pain of cardio-respiratory nature, than persons without a depressive or anxiety disorder. This warrants further research.